2021
DOI: 10.1177/11206721211001268
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib-related uveitis: A report of two severe cases

Abstract: Introduction: Ibrutinib is a small-molecule drug approved for the treatment of haematological disorders and is known to be associated with visual disturbances, but uveitis has not yet been reported as an adverse effect of this medication. We present two cases of ibrutinib-associated severe uveitis in patients with chronic lymphocytic leukaemia. Case description: Our first case is a 65-year-old woman who presented with acute onset of bilateral fibrinous anterior uveitis 1 day after starting ibrutinib. Her visio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…A case of severe sclerouveitis was described in a case study by Mehraban et al [ 61 ]. This is likewise corroborated by Bohn et al where they reported two severe cases of ibrutinib-related uveitis [ 62 ]. One patient was reported with an acute onset bilateral fibrinous anterior uveitis along with persistent subretinal fluid and hyperemic discs.…”
Section: Targeted Therapiessupporting
confidence: 77%
See 1 more Smart Citation
“…A case of severe sclerouveitis was described in a case study by Mehraban et al [ 61 ]. This is likewise corroborated by Bohn et al where they reported two severe cases of ibrutinib-related uveitis [ 62 ]. One patient was reported with an acute onset bilateral fibrinous anterior uveitis along with persistent subretinal fluid and hyperemic discs.…”
Section: Targeted Therapiessupporting
confidence: 77%
“…In a study by Bryd et al with a sample size of 391, Ibrutinib was found to have a cataract incidence rate of 3% [ 63 ]. Administration of oral and local topical steroids can be effective in treating symptoms, however, Bohn et al describes a case in which a patient reacted poorly to steroids and cessation of ibrutinib was ordered [ 62 ]. Fu et al , recommends screening with a slit lamp and dilated fundoscopic exam should be conducted [ 64 ].…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…The reason for ocular disturbances associated with ibrutinib is still unclear, but several mechanisms have been suggested. One case report showed a patient experiencing a spontaneous hyphema, which Bohn and colleagues attributed to ibrutinib's deficiency in platelet adhesion [ 7 ]. Levade et al found in vitro evidence that ibrutinib reduces platelet adhesion to von Willebrand factor and platelet aggregation induced by collagen [ 11 ], supporting this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients have complete resolution of symptoms upon discontinuation of ibrutinib and topical steroid eye drops (as shown in Table 1 ), similar to our patient. Some case studies have reported changing to different chemotherapeutic agents after discontinuation of ibrutinib [ 7 , 9 ], while others have restarted ibrutinib after their symptoms have resolved [ 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, ibrutinib-induced uveitis has been reported in only 3 case-reports (Arepalli et al, 2021;Bohn et al, 2021;Mehraban Far et al, 2021), in contrast with the 119 ICSRs documented in VigiBase. Selective pressure for Th1-mediated immunity has been proposed as a mechanism for ibrutinib-associated uveitis (Mehraban Far et al, 2021).…”
Section: Potential Safety Signalsmentioning
confidence: 99%